The effect of different herbicide on the number and activity of living microorganisms in soil - Sándor, Zsolt (Acta Agraria Debreceniensis, 2006)
Sustainable plant growth, considering the difficulties of weed elimination, cannot be effective without the application of herbicides. However, these chemicals have enormous ecological implications, including effects on the microbiological communities of soils. It is advisable to use herbicides that have minimal secondary effects on the environment and soil-living microorganisms. In contrast, herbicides with prolonged growth stimulating or inhibiting effects are not suitable, because both types have strong influences on the number and activity of bacteria, thus causing changes in the ecological equilibrium.Preceding small plot experiments, laboratory tests were carried out to study the effect of herbicides used in maize cultures on the number of bacteria and growth of microscopic fungi.Substances that were observed to have stronger influences were applied in small plot experiments set up in the experimental garden of the Department of Plant Protection of the University of Debrecen. We studied the effects of four herbicides (Acenit A88EC, Frontier 900 EC, Merlin SC and Wing EC) on the microbiological properties of the soil. These herbicides were used in different concentrations in maize culture, and we investigated the effects in different soil layers.In the laboratory experiments, we determined the total number of bacteria and microscopic fungi and examined the growth of Aspergillus niger, Trichoderma sp. and Fusarium oxysporum on peptone-glucose agar containing herbicides.During the small plot experiments, soil samples were collected 3 times a year from 2-20 cm depth. The total numbers of bacteria and microscopic fungi were determined by plate dilution method, while the method of most probable number (Pochon method) was used to determine the numbers of nitrifying bacteria and cellulose decomposing bacteria. To evaluate the microbiological activity of the soil samples we measured carbon-dioxide release (after 10 days incubation), nitrate production (after 14 days incubation) and the concentration of C and N in the biomass.We can summarize our results as follows:• In laboratory experiments, herbicides caused a decrease in the number of bacteria and inhibited the growth of microscopic fungi.• Frontier 900 EC and Acenit A 880 EC had the strongest inhibiting effect on microorganisms.• In small plot experiments, herbicide treatment decreased the total number of bacteria and microscopic fungi.• Herbicides caused a significant increase in the number of nitrifying and cellulose decomposing bacteria.• Different herbicides containing the same active compound had similar influences on soil microoorganisms.• A significant increase was observed in the physiological processes of tolerant microorganisms surviving the effects of herbicides